REINTERPRETASI PRINSIP KAFĀ’AH SEBAGAI NILAI DASAR DALAM POLA RELASI SUAMI ISTRI - Jahroh, Siti (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
Symptoms of domestic violence that occurs in marriage is due to the absence of equality or what is often called kafa>’ah in the fiqh al-muna>kahah between the prospective husband and wife. In this case the position of husband to wife is not equal, either in economic, social, education, culture, race/ethnicity, ancestry or religious level. Husband’s position which is not equivalent (as kufu>’) with his wife or vice versa, often triggers dispute between the two. Ongoing dispute, then followed by hurting words, beatings or physical abuse, irresponsible behavior, don’t meet the economic or biological needs, marry again, and even can also lead to a sadistic action or killing. In this perspective the author considers that if the value embodied in the kafa>‘ah concept is understood correctly and properly, it’ll actually give a positive chance to prevent domestic violence crime especially in the context of the relationship between husband and wife.[Gejala Kekerasan Dalam Rumah Tangga (KDRT) yang terjadi dalam perkawinan, salah satunya disebabkan tidak adanya kesetaraan atau yang sering disebut dalam fiqh al-munâkahah dengan istilah kafa>’ah antara calon suami dengan calon istri. Dalam hal ini posisi suami dengan istri yang tidak setara, baik setara secara ekonomi, sosial, pendidikan, kultur, ras/suku, keturunan maupun tingkat keberagamaan. Posisi suami yang tidak setara (se-kufu’) dengan istrinya ataupun sebaliknya, sering kali memicu perselisihan di antara keduanya. Perselisihan yang terus-menerus, kemudian diiringi dengan kata-kata yang menyakitkan, tindak pemukulan atau penganiayaan fisik, perilaku yang tidak bertanggung jawab, tidak memenuhi kebutuhan ekonomis atau biologis, kawin lagi, bahkan dapat pula menjurus pada tindakan sadisme dengan menyengsarakan atau menghilangkan nyawa. Dalam perspektif inilah penulis memandang bahwa nilai yang terkandung dalam konsep kafa>’ah jika dipahami dengan tepat dan benar sebenarnya berpeluang positif untuk menangkal tindak kejahatan KDRT terlebih dalam konteks relasi antara suami dan istri.]